Karakteristik dan Makna Rekreasi Pengunjung dalam Leisure dan Recreation di Tukad Bindu Kota Denpasar - Ramadhan, Shofyan Hadi; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2020)
Tukad Bindu at first was well-known as the dirty river and contained tons of household waste thrown away by society. Nevertheless, since 2018 it became one of recreation center in Denpasar City. Many activities carried out currently and the more crowded Tukad Bindu becomes, it is necessary to conduct a research which is expected to be able to perceive the characteristic and the meaning of recreation in Tukad Bindu to be a consideration for further development. The research method used is qualitative method with qualitative descriptive data analysis technique. The data resource of this research is from primary and secondary data. Data collection technique is conducted by observation, interview, questionnaire, and documentation. Sample determination is committed by accidental sampling using nonprobability sampling technique. Informant determination is committed by purposive sampling procedure. The result of this research indicates that progress level of Tukad Bindu is start on the development stage. The characteristics of Tukad Bindu visitors are perceived from socio-demographic characteristic, demographic characteristic, and psychographic characteristic turns out to be very diverse. The meaning of visitors’ recreation after having recreation in Tukad Bindy mostly are social meaning. Community should keep supporting activities committed by Tukad Bindu Foundation, particularly the youths there. It is expected that Tukad Bindu Foundation continues to hold regular annual events, such as Pekan Nusantara. Academics should synergize with each other in order to create an integrated recreation area among the fields of fishery, agriculture, and tourism.   Keyword :  Characteristics, The Meaning of Recreation, Leisure and Recreation